A study of epigenetic mineralisation in the Central Zone of the Damara Orogen, Namibia with special reference to gold, tungsten, tin and rare earth elements - Steven, Nicholas Macrae (Department of Geological Sciences, 2016)
Bibliography: pages 195-212.